Improving Net Photosynthetic Rate and Rooting Depth of Grapevines Through a Novel Irrigation Strategy in a Semi-Arid Climate - Ma, Xiaochi; Jacoby, Pete W.; Sanguinet, Karen A. (Frontiers in Plant Science, 2020)
Direct root-zone irrigation (DRZ) is a novel subsurface irrigation strategy initially tested in vineyards for economizing water and securing grape production in arid regions with unstable climatic patterns. However, studies are lacking on the responses of grapevine leaf carbon assimilation and deep rooting patterns to the novel irrigation strategy, which are essential for optimizing grapevine growth and alleviating extreme water stress during periods of heat and drought. Thus, a two-year field study was conducted in a commercial vineyard of Cabernet Sauvignon (Vitis vinifera L.) under a semi-arid climate in Washington, USA to compare the differences in leaf gas exchange and root distribution along the 0-160 cm soil profile, combined with measurements of specific leaf area and total carbon and nitrogen content in leaves and shoots to compare DRZ and traditional surface drip irrigation (SD) under three watering regimes. Compared to SD, significantly higher rates of net CO2 assimilation, stomatal conductance and transpiration in leaves, which positively correlated to midday stem water potential, were found in grapevines irrigated through DRZ in both years. Meanwhile, DRZ reduced total root number by 50-60% and root length density (RLD) by 30-40% in the upper 60 cm soil at high (0.75-0.80 crop evapotranspiration) and moderate (0.60-0.65 crop evapotranspiration) irrigation rates, but no significant differences were found at low (0.45-0.50 crop evapotranspiration) irrigation rate between DRZ and SD. Higher root number and RLD were detected under DRZ within 60-160 cm soil depths, accompanied by a decreased ratio of total carbon to nitrogen content in leaves with slightly increased specific leaf area. Decreased rainfall and increased temperature in 2018 possibly amplified the positive effects of DRZ. Our study indicates that grapevines under DRZ could develop deeper roots for water uptake, which helps ameliorate water stress and improve the photosynthetic rate as well as enhance grapevine adaptation to semi-arid climates.